Short-term effects of sacubitril/valsartan therapy on myocardial oxygen consumption and energetic efficiency of cardiac work in heart failure with reduced ejection fraction: A randomized controlled study - Nesterov, Sergey V. (John Wiley & Sons, 2025)
Aims
We sought to evaluate the mechanism of angiotensin receptor–neprilysin inhibitor (ARNI) sacubitril/valsartan therapy and compare it with a valsartan-only control group in patients with heart failure with reduced ejection fraction (HFrEF).
Methods and results
The study was a phase IV, prospective, randomized, double-blind, parallel-group study in patients with New York Heart Association class II–III heart failure and left ventricular ejection fraction (LVEF) ≤35%. During a 6-week run-in period, all patients received valsartan therapy, which was up-titrated to the highest tolerated dose level (80 mg bid or 160 mg bid) and then randomized to either valsartan or sacubitril/valsartan. Myocardial oxygen consumption, energetic efficiency of cardiac work, cardiac and systemic haemodynamics were quantified using echocardiography and 11C-acetate positron emission tomography before and after 6 weeks of therapy (on stable dose) in 55 patients (ARNI group: n = 27, mean age 63 ± 10 years, LVEF 29.2 ± 10.4%; and valsartan-only control group: n = 28, mean age 64 ± 8 years, LVEF 29.0 ± 7.3%; all p = NS). The energetic efficiency of cardiac work remained unchanged in both treatment arms. However, both diastolic (−4.5 mmHg; p = 0.026) and systolic blood pressure (−9.8 mmHg; p = 0.0007), myocardial perfusion (−0.054 ml/g/min; p = 0.045), and left ventricular mechanical work (−296; p = 0.038) decreased significantly in the ARNI group compared to the control group. Although myocardial oxygen consumption decreased in the ARNI group (−5.4%) compared with the run-in period and remained unchanged in the control group (+0.5%), the between-treatment group difference was not significant (p = 0.088).
Conclusions
We found no differences in the energetic efficiency of cardiac work between ARNI and valsartan-only groups in HFrEF patients. However, ARNI appears to have haemodynamic and cardiac mechanical effects over valsartan in heart failure patients.